Incidental findings in surveillence of paediatric Li Fraumeni patients – A single centre experience - Amy Alcock; Elizabeth McVittie; Zoe Nicholls; Hector Conti; Mark Davies; Rhian Isaac; Madeleine Adams (Rare)
Li-Fraumeni syndrome (LFS) is a rare cancer predisposition syndrome. Patients with LFS are at increased risk of early-onset tumours and undergo intensive radiological imaging surveillance to improve the early identification of malignancies. This report of a single-centre experience has shown that through surveillance imaging, especially whole-body MRIs, there is a high incidence of incidental findings. Incidental findings can result in anxiety and further evaluation often in the form of radiological imaging. It is important that patients and families are clearly counselled about incidental findings and findings of unknown clinical significance when undergoing imaging as part of a surveillance programme.